Interviewing interviewers: Collecting, analyzing and generalizing from occupational life histories of journalists. Issue 4 (2nd October 2017) - Meyers, Oren; Davidson, Roei
ABSTRACT: This article considers the implementation of the life history approach in the study of media professionals, based on an analysis of the occupational life histories of 77 active and former Israeli journalists. The article first discusses the decisions made throughout execution of the project. Next, it explores three key features of the dynamics of life history interviewing. Finally, the article examines the ways in which data gathered through life history interviews can be generalized.